Chitinase Activity in Healthy and Sclerotium rolfsii Infected Peanut - ENDANG PUDJIHARTATI; SISWANTO SISWANTO; SATRIYAS ILYAS; SUDARSONO SUDARSONO (Bogor Agricultural University, Indonesia, 2006)
The objectives of this experiment were to analyze the endo- or exo-chitinase activities of healthy and Sclerotium rolfsii infected peanuts. The experiment analyzed 24 different peanut genotypes. Results of the experiment showed chromogenic dimer was the most suitable substrate for analysing chitinase activities. Both endo- and exo-chitinases activities were detected in leaf, stem, and crown tissues. Increased in chitinase activities were detected in S. rolfsii infected peanut tissues than in healthy plant. Regression analysis showed negative slope between disease intensity and chitinase activity in S. rolfsii infected peanut tissue (R2= 0.45). Key words: Disease response, stem rot disease, endo- and exo-chitinase